EFFECTS OF KNOWLEDGE AND ATTITUDE ON USES OF MOBILE PHONE AMONG SELECTED CASSAVA FARMERS IN OYO STATE, NIGERIA - Ayandiji, A.; Oyesola, O. B. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2018)
This study determines the effect of knowledge and attitude on uses of mobile phone among selected cassava farmers in Oyo with a view to ascertain the farmers’ basic knowledge on mobile phone, determine the attitudinal disposition of farmers to the use of mobile phone and ascertain the sources of information of cassava farmers on basic applications on mobile phones. Hypotheses were tested on the level of knowledge and disposition of farmers on the use of mobile phone. The study was carried out in Oyo State using multi-stage sampling procedure and structured questionnaires to select 201 respondents from farmers who registered with the agricultural development programme, three Local governments was selected from one senatorial district, five wards from each local government and five villages from each ward. Data collected were analyzed using descriptive and inferential statistics. There were high knowledge (94.5%) about the basic application of mobile phone and generally all respondents were favourably disposed to the use of mobile phone in the study area. Respondents basic knowledge about mobile phone has great influence on the level of use (r = 0.230; p < 0.005), and attitude (r = 0.230; p < 0.005) has a favourable disposition on the use of mobile phone. There is high level of knowledge and favourable attitude towards mobile phones. However, more training programmes for farmers in some other applications are highly required.